2007
DOI: 10.1002/lsm.20417
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between collagen solubility and skin optical clearing using sugars

Abstract: Background and Objective: Light scattering from collagen within skin limits light-based therapeutics while increasing the risk of epidermal thermal injury. Specific chemicals show the ability to reduce light scattering by reversibly altering the optical properties of skin. This study examines the correlation between collagen solubility and the optical clearing potential (OCP) of sugars and sugar-alcohols using in vitro rodent skin. Materials and Methods: Collagen solubility in dextrose, fructose, sucrose, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 23 publications
(34 reference statements)
1
66
0
3
Order By: Relevance
“…Since the RI of OCA is higher than the RI of water, the OCA inclusion in the tissue provides the RI matching mechanism. 15, 24 An increase in tissue transparency is achieved 11 and better contrast images can be obtained from deeper layers inside the tissue. 7 Many studies with di®erent kinds of tissues and OCAs like glycerol, 25,26 glucose 11,27 or dimethyl sulfoxide 14 have been made in the last two decades.…”
Section: Introduction and Basic Conceptmentioning
confidence: 99%
“…Since the RI of OCA is higher than the RI of water, the OCA inclusion in the tissue provides the RI matching mechanism. 15, 24 An increase in tissue transparency is achieved 11 and better contrast images can be obtained from deeper layers inside the tissue. 7 Many studies with di®erent kinds of tissues and OCAs like glycerol, 25,26 glucose 11,27 or dimethyl sulfoxide 14 have been made in the last two decades.…”
Section: Introduction and Basic Conceptmentioning
confidence: 99%
“…8 We introduced collagen solubility as a measure of a chemical agent's ability to screen noncovalent forces and correlated it with tissue optical clearing for a series of polyols and sugars. 5,9 These studies suggested that, of the chemical agents in the series, their optical clearing potential ͑and collagen solubility͒ could be grouped by chain length and locations of hydroxyl groups within the molecule. More specifically for sugar alcohols, optical clearing potential for the series could be grouped by chain length, in increasing order, as two-carbon backbone ͑ethylene glycol͒, three-to five-carbon backbone ͑glycerol to xylitol͒, and six-carbon backbone ͑sorbitol͒.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in BGC leads to a subsequent rise in the refractive indices of blood and interstitial fluid, whereas the refractive index of scattering particles in the skin remains unchanged. 51,52 Thus, the refractive index mismatch between the solute and the particles diminishes and the scattering is decreased, which was clearly reflected in the OCT signal slopes.…”
Section: Correlation Between Octss and Bgcmentioning
confidence: 99%
“…In addition, the interaction between collagen and OCAs can also lead to a substantial reduction in tissue light scattering. [51][52][53] Thus, there would be more effective light dose penetrating through the SC and the epidermis into the lower dermis area, where blood in the skin tissue is much more abundant. The probing depth of OCT was increased when the glycerol optical clearing agent was applied topically on the skin.…”
Section: Correlation Between Octss and Bgcmentioning
confidence: 99%